The Logic of Unconditional Love: A Structural and Theological Analysis of the Parable of the Prodigal Son in Luke 15:11-32 - PATANDEAN, Yohanis Enci; JENITA, Theresia (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2025)
This study addresses the social value of understanding unconditional love, forgiveness, and repentance as depicted in the Parable of the Prodigal Son in Luke 15:11-32 and the scientific value of bridging the knowledge gap regarding the logical analysis of its narrative structure. While previous studies have emphasized theological and moral aspects, a logical approach to examining the narrative, character relationships, and cultural symbolism has been limited. This research analyzes the narrative logic structure within the Parable of the Prodigal Son in Luke 15:11-32. It seeks to uncover the relationship between Jewish cultural symbolism and the theological message and to explain the implications of the father-younger son-older son dynamic for understanding the human-God relationship. The study focuses on the biblical text of Luke 15:11-32 within the cultural and historical context of first-century Judaism. A qualitative research approach employed narrative text analysis and literature study. Data analysis involves structural breakdown, semiotic analysis, and theoretical triangulation, referencing narrative theory and the concept of paradoxical logic. The study reveals that the parable’s narrative structure is logically constructed to challenge conventional understandings of justice, love, and the divine-human relationship. It identifies key elements such as the disruption of initial equilibrium through the younger son’s request for inheritance, the climax of his degradation, and the resolution in the father’s welcoming response. The analysis also highlights the theological paradoxes of humility versus divine honor, justice versus forgiveness, and repentance versus grace.